Compatibility of the Use of Generic and Non-Generic Drugs with Hospital Formularies at the Outpatient Installation of Oto Iskandar Dinata Soreang Hospital - Sulaiman, Nur Asisah M.; Rosmiati, Meiti (Journal of Scientific Insights, 2025)
Health is the most important things for every individual to play an active role in social life and contribute to economics development. One of the most important aspects of efforts to achieve health is the use of good, correct and rational medicine. Generic drugs that have almost equivalent to marcated drugs have been required to be used by the Government as one of the strategies to increase access to more affordable health services. The purpose of this study is to examine the pattern of use of generic and non-generic drugs in outpatients ward at Oto Iskandar Dinata Soreang Hospital during the period from December 2024 to February 2025. The research data used in this study is with a quantitative descriptive approach by examining prescriptions and then analyzing them and then adjusting them to the formularies available at the Hospital.